L’intégration du monde rural - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
L’intégration du monde rural dans le monde urbain est irréversible. ' Extrait de Vues du Sud, IRAM/L’Harmattan, 1998.